Le privilège optique : Éthique du voyage et esthétique de la vision chez Nerval - Jacob Lachat (Viatica)
In Journey to the Orient, published in 1851, Nerval adopts a way of travelling similar to his way of seeing. Placing his story on the cusp of “revelation literature”, the writer strives to portray preestablished travel images in a different way. Seeking both to surprise himself and his reader, Nerval never ceases to navigate in a random and hazardous manner and to visualise through mediation the foreign cities he passes through. Bearer and defender of the notion of vision, the traveller also tries to demonstrate a travel ethic that is opposed to the conventions of the time.